Optimal hedge ratio and the hedging performance of commodity futures: the case of Malaysian crude palm oil futures market - Islam, Mohd Aminul (Euro Asia Research and Development Association EARDA, 2017)
This paper aims to examine the hedging performance of the crude palm Oil futures Market in Malaysia. The optimal hedge ratios and the hedging performance are examined for two different futures contracts denoted as futures 1 and futures 2 using daily settlement prices from January 4, 2010 to October 31, 2017. Four econometric models comprising of the standard ordinary least square (OLS), vector auto-regression (VAR), vector error correction model (VECM) and the bivariate generalized autoregressive conditional heteroscedasticity (BGARCH) models are employed to compute hedge ratios. The first three models estimate constant hedge ratios while the last model estimates time varying hedge ratio. The effectiveness of the hedge ratios for two contracts is evaluated in terms of in-sample and out-of-sample performance. For in-sample performance, January 4, 2010 to October 31, 2016 period is used while for out-of-sample validation, a one year data from November 2016 to October 31, 2017 is used. The empirical results show that the bivariate GARCH model performs better in the reduction of risk for both periods and the nearest futures contract (next one month contract) appears to be better in hedging than the far futures contract (next two month contracts). This suggests that the investors can use crude palm oil futures contract particularly the nearest futures contract as an effective instrument to hedge the risk and the bivariate BEKK-GARCH as an efficient model for designing hedging strategy.